ANALISIS WACANA KRITIS BERITA MENGENAI PENDATANG PASCALEBARAN TAHUN 2010 PADA SURAT KABAR â€œBALI POSTâ€ - Utama, I Dewa Gede Budi (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2012)
Critical Discourse Analysis is one of the models of discourse analysis. The analysis model in the currentstudy tries to describe some news in â€œBali Postâ€ about new comers who come to Bali after Lebaran 2010.Those news describe them negatively by giving them negative identification through discourse strategies. Themain objective of this research is to describe the description of actor in the news and to know the journalistsâ€™ideology behind their news by using Theo van Leeuwen analysis model.Keywords: critical discourse analysis, discourse strategies based on Theo van Leeuwen model, idiology